Improving librarianship skills through P3KNK community service at Universitas Islam Bandung library - Raysa Atripa Royyan; Salwa Ghaida Rakhmawati; Yezika Rachman; Riche Cynthia Johan; Atty Sofiyanty (Universitas Pendidikan Indonesia, 2025)
The Program Penguatan Profesional Kepustakaan Non Kependidikan (P3KNK) is an experiential learning-based community service model designed to strengthen students' professional competencies through direct involvement in librarianship practices. This article examines how implementing P3KNK in library collection procurement and development activities contributes to improving students' librarianship competencies at Universitas Islam Bandung library. This article is reviewed using a qualitative descriptive approach that involves students as active participants in library operations. Data were collected through observation, documentation, and student reflection during the program. The results of the community service indicate a significant increase in three main competency areas: conceptual knowledge related to collection management, technical skills in the procurement and processing of library materials, and professional attitudes, such as responsibility and collaboration. The implementation of P3KNK at the Universitas Islam Bandung library not only enhances students' readiness for professional practice but also makes a tangible contribution to partner institutions by supporting collection development. P3KNK can be positioned as an effective community service model that bridges theoretical learning and librarianship practice and contributes to improving the quality of librarianship education in higher education. Abstrak Program Penguatan Profesional Kepustakaan Non Kependidikan (P3KNK) merupakan model pengabdian kepada masyarakat berbasis experiential learning yang dirancang untuk memperkuat kompetensi profesional mahasiswa melalui keterlibatan langsung dalam praktik kepustakawanan. Artikel ini mengkaji bagaimana pelaksanaan P3KNK pada kegiatan pengadaan dan pengembangan koleksi perpustakaan berkontribusi terhadap peningkatan kompetensi kepustakawanan mahasiswa di Perpustakaan Universitas Islam Bandung. Artikel ini dikaji dengan menggunakan pendekatan deskriptif kualitatif dengan melibatkan mahasiswa sebagai partisipan aktif dalam aktivitas operasional perpustakaan. Data dikumpulkan melalui observasi, dokumentasi, dan refleksi mahasiswa selama program berlangsung. Hasil pengabdian menunjukkan adanya peningkatan yang signifikan pada tiga aspek kompetensi utama, yaitu pengetahuan konseptual terkait manajemen koleksi, keterampilan teknis dalam proses pengadaan dan pengolahan bahan pustaka, serta sikap profesional seperti tanggung jawab dan kemampuan bekerja sama. Pelaksanaan P3KNK di Perpustakaan Universitas Islam Bandung tidak hanya meningkatkan kesiapan mahasiswa dalam praktik profesional, tetapi juga memberikan kontribusi nyata bagi institusi mitra melalui dukungan terhadap proses pengembangan koleksi. P3KNK dapat diposisikan sebagai model pengabdian yang efektif dalam menjembatani pembelajaran teoretis dan praktik kepustakawanan serta berkontribusi pada peningkatan kualitas pendidikan kepustakawanan di perguruan tinggi. Kata Kunci: kompetensi kepustakawanan; pengabdian kepada masyarakat; perpustakaan perguruan tinggi